Lithium-ion Diffusion in Solid Electrolyte Interface (SEI) Predicted by Phase Field Model. Issue 1753 (11th February 2015) - Guan, Pengjian; Liu, Lin
ABSTRACT: Solid electrolyte interface (SEI) layer plays a key role in lithium-ion batteries' degradation research. However, SEI layer microstructure prediction still needs further investigation, especially the lithium-ion diffusion in SEI layer considering its morphology evolution during the growth of SEI. Due to the unique advantage of avoiding explicitly tracking the interfaces with sharp composition gradients, a phase field model is developed to simulate the SEI formation and its morphology evolution that is regarded as a solidification process. Fick's law and mass balance are applied to investigate lithium-ion concentration distribution and diffusion coefficients of different SEI layers (i.e., compact and porous SEI layers) predicted by the developed phase field model. The simulation results show lithium-ion diffusion coefficients between 298K and 318K are 1.34-1.87(10 -16 ) m 2 /s and 1.73-2.18(10 -12 ) m 2 /s for compact SEI and porous SEI layer, respectively. The developed model has great potential to be extended to three dimensional spaces for SEI layer spatial growth investigation and other interfaces with complex morphology evolution.